When should a patient with community‐acquired pneumonia (CAP) be admitted to the hospital?. Issue 8 (August 2015) - Sidana, Anshu; Gomez, Luis; Achkar, Morhaf Al
Abstract : Evidence‐Based Answer : Severity of illness and prognostic models effectively predict mortality risk in patients with CAP (SOR: A, high‐quality prospective cohort studies). CAP patients with higher risk according to these scoring systems should be admitted (SOR: C, consensus guidelines).